Harmony in three poets’ writings (Abai, Lermontov, Byron) (Journal of Philosophy Culture and Political Science, 2019)
Currently, in the period of development of the Kazakh national identity as well as in preserving the national code and defining cultural boundaries, the study of the translation of historical-cultural and emotional concepts in unrelated languages, in order to identify the similarities and differences in the translation of Abai’s poem “My soul is dark …” in Kazakh and Russian languages with the original work in English are defined as the aims and tasks of this article.Consideration of the content and importance of the era of Abai and his heritage are revealed in conjunction with the works of Lermontov and Byron which followed by determining the research hypothesis in concretizing the spiritual relationship in the formation of national and cultural consciousness in the global universe.Based on the figurative perception and cultural concepts of Abai’s translation in the philosophical and cognitive aspects, the cultural concepts in Kazakh, Russian and English languages are defined with the usage of lingua-cultural comparative methods and hermeneutical analysis. In the process of analyzing, within the framework of Abai’s legacy, the results of Kazakh and western studies’ results are taken as the basis of a given article so far.Key words: translation, national-cultural concepts, emotional concept, intercultural language communication.